2013
DOI: 10.4103/2278-9626.115999
|View full text |Cite
|
Sign up to set email alerts
|

A study of different modes of disinfection and their effect on bacterial load in dental unit waterlines

Abstract: Objective: To compare the effect of disinfection of dental unit waterlines (DUWLs) on bacterial load using disinfection methods and agents like 0.12% chlorhexidine gluconate (CHX), time-dependent flushing (1 min, 2 min), and using distilled water and tap water as water sources. Materials and Methods: Four dental units were taken: Unit A contained 0.12% CHX, Unit B contained distilled water, Unit C contained tap water, and Unit D included flushing for 1 and 2 min. A total of 36 wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In various countries, dental procedures were banned entirely to prevent viral transmission, thus creating a huge financial implication for dental professionals. The infection control during dental healthcare amid the COVID-19 pandemic is demonstrated in Table 6 [96][97][98][99][100][101]. In terms of the psychological impact of COVID-19 on dental personals, Khanagar et al reported increased mental stress and psychological distress among dentists [102].…”
Section: Economic and Emotional Impact On Dentists And Dental Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In various countries, dental procedures were banned entirely to prevent viral transmission, thus creating a huge financial implication for dental professionals. The infection control during dental healthcare amid the COVID-19 pandemic is demonstrated in Table 6 [96][97][98][99][100][101]. In terms of the psychological impact of COVID-19 on dental personals, Khanagar et al reported increased mental stress and psychological distress among dentists [102].…”
Section: Economic and Emotional Impact On Dentists And Dental Practicesmentioning
confidence: 99%
“…The infection control during dental healthcare amid the COVID-19 pandemic is demonstrated in Table 6 [ 96 , 97 , 98 , 99 , 100 , 101 ]. In terms of the psychological impact of COVID-19 on dental personals, Khanagar et al reported increased mental stress and psychological distress among dentists [ 102 ].…”
Section: Economic and Emotional Impact On Dentists And Dental Practicesmentioning
confidence: 99%
“…Ensuring quality of dental unit water reduces bioburden in aerosols. Dental unit waterlines promote bacterial growth and development of biofilm due to the presence of long narrow-bore tubing, inconsistent flow rates, and the potential for retraction of oral fluids from hand pieces into the unit tubing 32. .…”
mentioning
confidence: 99%
“…A infecção natural pode ocorrer pela inoculação percutânea, inalação ou ingestão, e também é de interesse como uma potencial arma biológica. (LIMMATHUROTSAKUL et al, 2013;MASSEY et al, 2014 , 1986;WILLIAMS et al, 1993;TALL et al, 1995;BARBEAU et al, 1996;SHEPHERD et al, 2001;SZYMAŃSKA, 2007;WATANABE, 2007;UZEL;COGULU;ONCAG, 2008;SINGH;NAGARAJA;HUNGUND, 2013;SZYMAŃSKA;SITKOWSKA, 2013;DALLOLIO et al, 2014 (SINGH et al, 1997;SILVEIRA;HUSAIN, 2008;CASTRO;OLIVEIRA;LOPES, 2013).…”
Section: Discussionunclassified